Problems Of Environmental Biosafety in Its Parasitic Pollution (Texas Journal of Medical Science, 2024)
The profound civilizational shift of recent decades has increased the anthropogenic impact on the biosphere and complicated the environmental situation. Human impacts on the environment lead to a sharp disruption of the evolutionarily established balance of ecosystems at different levels, including parasitic ones. Parasitic systems in modern farming conditions respond to external influences with a complex of reactions, a significant part of which are unstudied. This problem relates to the field of ecology and combines theoretical and practical aspects of solving the problem of environmental biosafety during parasitic contamination.